Construction of Political Identity on Instagram: Unveiling the Kadrun Hashtag Movement in Indonesia's 2024 Presidential Election: Konstruksi Identitas Politik di Instagram: Menyingkap Gerakan Tagar Kadrun dalam Pemilihan Presiden 2024 di Indonesia - Ferry Adhi Dharma; Didik Hariyanto; Fajar Muharram (Universitas Muhammadiyah Sidoarjo, 2023)
This scientific article investigates the construction of political identity through hashtag movements on Instagram, focusing on the kadrun